อัตลักษณ์และการท่องเที่ยว : ศึกษากรณี ผู้ไทบ้านภู ตำบลบ้านเป้า อำเภอหนองสูง จังหวัดมุกดาหาร - พรรณปพร ภิรมย์วงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The primary purpose of thesis is to study identity and Phuthai ethnic group of Banphu on their daily life in the context of tourism. The study employs the concepts of identity and ethnicity, to consider tourism activities in Banphu as drama and as phenomenon of globalization. Qualitative method was used to collect data with emphasis on participant observation and interviews. In-depth interviews of key informants were extensively carried out. The study found that identity in daily life of the Phuthai at Banphu is a dynamic, and fluid depending on the context and situation of specific social interaction. Nevertheless the villagers can express their personal identity without reference to the collective identity, collective identity still influences the realization and performance of personal identity. Identity of the Phuthai people at Banphu in the context of tourism can be seen clearly in the form of group identity that represents the image of the Phuthai at the village level, i.e. Phuthai style of dressing and the Phuthai traditional dance. In the context of tourism, individual identity is expressed commonly through identity as it has been considered a standard native village identity. Government policies and the role of public officials is an important part in revival of the local identity of the Phuthai at Banphu